HAEMATOLOGICAL AND BIOCHEMESTRY SERUM VALUES OF COMMON WOLLY MONKEY (Lagothrix lagotricha) REAREDIN SEMI-CAPTIVITY IN THE PERUVIAN TROPICS - Rodríguez H., Katherine (2014)
The objective of this study was to determine the haematological and serum biochemistry values in a population of woolly monkeys choros (Lagothrix lagotricha)reared in semi-captivity at the Centro de Rescate y Rehabilitación Ikamaperu in Lagunas, Loreto, Peru. Forty primates, 12 males and 28 females, which included juveniles, subadults and adults in apparent good health conditions were sampled. The haematological values were similar, triglyceride and AST values were elevated, and total protein and ALP values were low as compared to other studies in zoos. The age group influenced erythrocyte counts, total protein, total bilirubin, cholesterol and alkaline phosphatase. No sex effect was found on erythrocytes, leukocytes and platelet counts and in serum chemistry values, except for the number of monocytes.